Optimal Cerebral Perfusion Pressure Targeted Patient-specific Treatment of Severe TBI in ICU. (16th November 2020) - Krakauskaite, Solventa; Petkus, Vytautas; Preiksaitis, Aidanas; Chomskis, Romanas; Zubaviciute, Erika; Vosylius, Saulius; Rocka, Saulius; Rastenyte, Daiva; Ragauskas, Arminas
Abstract: INTRODUCTION: Determination of patient-specific management methodology is crucial for patients with traumatic brain injury (TBI). The treatment outcomes of TBI patients depend on impairments of cerebral blood flow autoregulation that may be affected by patient's age, brain injury grade or pharmacological influences, and other factors. METHODS: Multimodal ABP, ICP, CPP and CA monitoring of 81 TBI patients have been performed at Republic Vilnius University Hospital (Lithuania). ICM + software (Cambridge, UK) was used for continuous CA status assessment by identification of Pressure Reactivity Index (PRx) and patient-specific optimal CPP (optCPP). The post-hoc analysis of associations between the patients' outcome and complex influence of monitored parameters have been carried out by creating multifactorial model to predict TBI patient's outcome and to determine factors influencing outcome. RESULTS: The multifactorial logistic regression model showed that the most significant factors affecting TBI patient's outcome are an age, Glasgow Coma Scale (GCS), glucose level in blood serum samples (determined within 24 hours after admission), Helsinki CT (HCT) score and duration of the longest CA impairment when PRx(t)>0.5 within 24 hours after admission. CONCLUSION: The main factors affecting TBI treatment outcomes are patient's age, HCT, GCS, blood glucose level and the CA status during the first day after admission. The optCPP-targeted patient-specific management is useful for stabilizing CA in severe TBI patients as well as for improving outcome for younger patients with age <45.